Kinerja Pegawai Dalam Pelaksanaan Pelayanan Publik Di Kantor Kecamatan Sungai Tabuk Kabupaten Banjar Kalimantan Selatan - Sugiannor, Sugiannor; Kuncoro, Decky; Junaidy, Junaidy (Program Studi Ilmu Pemeritahan Fakultas Ilmu sosial dan Ilmu Politik Universitas 17 Agustu, 2020)
Assesment of public service rendered by the government depending on his employee performances. Performances employees in public service can be seen through some performance indicators. Indicators used to rate employees performance Sungai Tabuk sub district included, responsiveness, responsibility, and accountability. All three indicators will be used for as a basic judging the performances employees in providing public services. To answer research questions, the researcher uses a qualitative descriptive methode. Research has shown that employees performances in public services is good enough. There are a few point that make a good record in this research; 1) Staff responsibility discriminatory in rendering services; 2) Employee response to community service has been adjusted with the urgency situation; 3) Accountability of employee performance in giving service, have conformed to the applicable values and norms of society. Its intended value and norms is berelaan, bubuhan, gawi manuntung, dalas belangsar dada, and bisa-bisa maandak awak. In an effort to improve performance to achieve good public service, there are certain obstacle in particular that deal with the lack of public knowledge of the conditions to be prepared, and the undisciplined of an employee when it comes to working hours.